(untitled) (Communications in Computational Physics, 2022)
The discontinuous Galerkin finite element method (DG-FEM) is a high-precision numerical simulation method widely used in various disciplines. In this paper, we derive the auxiliary ordinary differential equation complex frequency-shifted multi-axial perfectly matched layer (AODE CFS-MPML) in an unsplit format and combine it with any high-order adaptive DG-FEM based on an unstructured mesh to simulate seismic wave propagation. To improve the computational efficiency, we implement Message Passing Interface (MPI) parallelization for the simulation. Comparisons of the numerical simulation results with the analytical solutions verify the accuracy and effectiveness of our method. The results of numerical experiments also confirm the stability and effectiveness of the AODE CFS-MPML.